Рецензия на учебно-методическое пособие В. Ф. Сухиной "Экологическое образование и воспитание. практическое внедрение в учебный процесс интегрированной программы экологического образования и воспитания". Saarbrucken (Германия): изд-во Laplambert Academic Publishing, 2014. – 161 с. - Безродный, Андрей Геннадиевич; Тарароев, Яков Владимирович (НТУ "ХПИ", 2016)
Рассматриваемое нами учебно-методическое пособие «Экологическое образование и воспитание» является обобщающим результатом совместной деятельности творческого коллектива учителей СЭПШ (специализированной экономико-правовой школы при Народной украинской академии) и преподавателей НУА под общим руководством доктора философских наук, профессора В. Ф. Сухиной. Данное издание вобрало в себя множество теоретических и апробированных на практике в процессе непосредственного задействования в учебный процесс авторских наработок в области экологического образования и учитывает специфику как самого курса, так и специфику места его разработки и преподавания.

The contact teaching manual "Environmental education and training" is a general result of the joint activity of the creative team of teachers SELS (Specialized Economics and Law School at the Ukrainian People's Academy) and teachers UPA under the overall supervision of Doctor of Philosophy, Professor V.F. Sukhinoj. This edition has incorporated a lot of theoretical and tested in practice in the process of direct engagement in the learning process of copyright developments in the field of environmental education, and takes into account the specifics of both the rate and specificity of the place of its development and teaching. Peer reviewed papers - one of the results of pedagogical experiment on continuing education, which is carried out in the People's Ukrainian Academy since 1997. At present, the UPA has been building a working model of non-traditional educational institution, which is based on the idea of continuous education - from pre-school to post-graduate, education "through life". It is the realization of this idea, according to V. F. Sukhina, significantly closer to the implementation of the goals and tasks facing the entire education system. The main purpose of this book - to contribute to the formation of ecological outlook of students. And this goal, we believe, been achieved. We believe that regardless of curricula given material will be useful to all who work in the field of education and concerned about the survival of humanity.
Review at teaching aids of V. F. Sukhina "Environmental education and training of practical implementation in the educational process integrated programs of environmental education and training". Saarsbrucken (Germany): Laplambert Academic Publishing, 2014
Keywords: природопользование; программа образовательная; гуманизация; environmental management; educational program; humanization